miR-431 secreted by human vestibular schwannomas increases the mammalian inner ear’s vulnerability to noise trauma - Fujita, Takeshi; Seist, Richard; Kao, Shyan-Yuan; Soares, Vitor; Panano, Lorena; Khetani, Radhika S.; Landegger, Lukas D.; Batts, Shelley; Stankovic, Konstantina M. (Frontiers in Neurology, 2023)
This is a provisional file, not the final typeset article Results: Differentially expressed microRNAs included hsa-miR-431-5p (enriched in VS-PH) and hsa-miR-192-5p (enriched in VS-GH). Newborn mice receiving intracochlear injection of viral vectors over-expressing hsa-miR-431-GFP, hsa-miR-192-GFP, or GFP only (control) had similar hearing 6 weeks post-injection. However, after acoustic trauma, the miR-431 group displayed significantly worse hearing, and greater loss of synaptic ribbons per inner hair cell in the acoustically traumatized cochlear region than the control group.Conclusions: Our results suggest that miR-431 contributes to VS-associated hearing loss following cochlear stress. Further investigation is needed to determine whether miR-431 is a potential therapeutic target for SNHL.